The psychosocial problems of children with narcolepsy and those with excessive daytime sleepiness of uncertain origin. - Stores, G; Montgomery, P; Wiggs, L (2006)
BACKGROUND: Narcolepsy is a predominantly rapid eye movement sleep disorder with onset usually in the second decade but often in earlier childhood. Classically it is characterized by combinations of excessive sleepiness especially sleep attacks, cataplexy, hypnagogic hallucinations, and sleep paralysis. The psychosocial effects of this lifelong condition are not well documented, especially in children. This study aims to describe the psychosocial profile of a large group of children with narcolepsy compared with other excessively sleepy children and controls. METHODS: We used an international cross-sectional questionnaire survey of children aged from 4 to 18 years who had received from a physician a diagnosis of narcolepsy compared with age- and gender-matched controls. Assessments were made of behavior, mood, quality of life, and educational aspects. RESULTS: Recruited children were separated into those who met conventional criteria for narcolepsy (n = 42) and those whose primary complaint was excessive daytime sleepiness without definite additional features of narcolepsy (excessive daytime sleepiness group; n = 18). Compared with controls, children with narcolepsy and also those with excessive daytime sleepiness alone showed significantly higher rates of behavioral problems and depression. Again, to a significant extent, their quality of life was poorer and they had more educational problems. The children with narcolepsy and the excessive daytime sleepiness group were indistinguishable from each other on these measures. CONCLUSIONS: A range of psychosocial problems can be identified in children with narcolepsy. The origins of these problems are unclear. The similar profiles of difficulties in the narcolepsy and excessive daytime sleepiness groups suggest that excessive sleepiness is the main cause. Clinicians and others responsible for the care of such children need to be mindful of the importance of early detection, intervention, and, ideally, the prevention of these problems.